Recognition and distribution of Leptodactylus mystaceus (Anura; Leptodactylidae) in the State of São Paulo, Southeastern Brazil - Toledo, Luís Felipe [UNESP]; Castanho, Luciano Mendes; Haddad, Celio Fernando Baptista [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2005)
Leptodactylus mystaceus, uma espécie com ampla distribuição geográfica pela América do Sul, é diagnosticada com base em exemplares do Estado de São Paulo, seu limite meridional de distribuição geográfica. Apresentamos aqui o primeiro registro da espécie para o Sudeste do Brasil, ampliando sua distribuição conhecida em cerca de 1.300 km ao sudeste. Também incluímos a descrição da vocalização de anúncio, informações sobre história natural, fotografia em vida e desenhos de caracteres morfológicos que auxiliam na identificação desta espécie.

Leptodactylus mystaceus, a widespread species over South America, is diagnosed based on specimens from the State of São Paulo, its southernmost geographic distribution limit. Here we present the first record of this species for Southeastern Brazil, extending its distribution for approximately 1,300 km to the southeast. We also include a description of its advertisement call, natural history data, photograph in life and morphological illustrations that make easier the identification of the species.
Keywords: Distribuição geográfica; vocalização de anúncio; Leptodactylus mystaceus; Geographic distribution; advertisement call; Leptodactylus mystaceus